Konsep dan Sistematika Pemikiran Fiqih Sufistik Al-Ghazali - Masburiyah Masburiyah (NALAR FIQH: Jurnal Hukum Islam, 2011)
Al-Ghazali was one of a philoshoper, theologian faqih and sufi. One of the famous ulama in mid-fifth century until the early development of Islamic law in the era decline of the science of fiqh. In those days he was known as fuqaha who combines discussion of fiqh and Sufism, at which time there a conflict between fiqh scholar and sufi group. In the span of a long history between fiqh and Sufism eventually occur very good relationship.